Use of Flat Up Learning Media Improves Learning Outcomes - Haning Margi Betasari (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This article considers the use of the learning media as a tool to make it easier to deliver learning materials. The learning media is designed to the best possible so that learners can more easily understand the learning materials. Additionally, the use of teaching media can provide learners with the motivation to learn better. Learners can also create learning mediums especially on flat building materials so they can closely observe the media they have. Thus learners will better understand the learning materials and learning results can improve to a maximum.